Forecasting Output and Inflation: The Role of Asset Prices - Stock, James H.; Watson, Mark W. (Journal of Economic Literature, 2003)
Are asset prices useful predictors of inflation and real output growth? After reviewing the large literature on this topic, we undertake an empirical analysis of quarterly data for seven OECD countries spanning 1959-99. The literature review and the empirical analysis yield the same conclusions. Some asset prices predict inflation or output growth in some countries in some periods. Which series predicts what, when, and where is difficult to predict; being a good predictor historically is largely unrelated to subsequent performance. Intriguingly, forecasts that combine these individually unstable forecasts appear to improve reliably upon univariate benchmarks.